Fundamentals of the Islamic Medical Philosophy - Shogar, Shogar; A, Ibrahim (IIUM Medical Journal Malaysia, 2018)
The purpose of this paper is to advocate for a holistic medical philosophy that is capable of accommodating various models of medical explanations. Such a comprehensive and integrated approach of medical philosophy should be capable of addressing, the ethical, epistemological and metaphysical aspects of medical research and practice. The basic presupposition of the paper is that the Islamic principles on health promotion can play an important role in developing such a holistic medical philosophy. Adopting the analytic method, the paper investigates the three major frameworks of explanation that dominated the history of medical philosophy: (a) the humoral model that is based on balance of the humors; (b) the biocentric model which is based on causal explanation and defines disease in descriptive biological terms; and (c) the postmodern or meta-biocentric model that concerned mainly with the medical philosophy and aims at promoting the holistic approach. This paper, also, investigates the three basic forms of medical explanations which are determined by the above domains, i.e. the descriptive, the normative, and the integrated models. The paper traces the impact of explanation methods on good medical practices and explores the Islamic medical philosophy and its potential role in promoting the holistic approach. Along the way, the paper discusses the ideal relationship between physician and patient according to the Islamic perspective.